Strategi Komunikasi Public Relation Agency sebagai Konsultan dalam Menangani Kebutuhan Klien di Industri Teknologi - Mutiara Dwi Putri; Ika Sartika; Renny Soelistiyowati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study analyzes the communication strategies of PR agencies that act as consultants in supporting the needs of clients in the technology industry. This research uses a descriptive qualitative approach through in-depth interviews with KlikPR managers and direct observation. The findings show that KlikPR's communication strategy follows three communication objectives, namely to secure understanding, to establish acceptance, and to motivate action. KlikPR prioritizes open communication, regular coordination, and participatory work practices to strengthen relationships with clients. This strategy is based on the theory of organizational communication flow through the aspect of downward communication, which serves to convey strategic directions and context, while upward communication facilitates the exchange of ideas, reporting, and evaluation. With an integrated and transparent communication approach, KlikPR is able to maintain client trust and build long-term partnerships.